Guerra, racionamento, distinção social : o cotidiano de Copacabana, Ipanema, Leme durante a Segunda Guerra Mundial - Klever, Lucas de Oliveira (2020)
The present work presents the daily life of the Rio de Janeiro elite of Copacabana, Ipanema, Leme (CIL community), during the rationing period related to the Second World War, through the newspaper Beira-Mar (1942-1945) and the Jornal do Brasil, in counterpoint, since the target public of JB was broader, including the popular and middle classes, in addition to the elite. The theoretical contribution is based on authors such as: Pierre Félix Bourdieu, Norbert Elias, Agnes Heller, Tânia Regina de Luca, Lúcia Lippi de Oliveira, Thorstein Veblen, Georg Simmel. Through newspaper articles, decree-laws are exposed, the creation of the image of the distinction of the south zone, elite sports, automobiles, clubs, events, charitable actions, blackouts, advertisements, which reinforced the normality of CIL during the worldwide conflict and also the maintenance of distinguishing practices.